2018
DOI: 10.1111/nyas.13965
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping vitamin A interventions in the United States, Guatemala, Zambia, and South Africa: case studies

Abstract: Vitamin A (VA) deficiency is a serious public health problem, especially in preschool children who are at risk of increased mortality. In order to address this problem, the World Health Organization recommends periodic high‐dose supplementation to children 6–59 months of age in areas of highest risk. Originally, supplementation was meant as a short‐term solution until more sustainable interventions could be adopted. Currently, many countries are fortifying commercialized common staple and snack foods with reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…In Zambia, VAD has been addressed as a problem of public health significance, leading to different approaches that include vitamin A capsule supplementation targeting since 1990 children aged 6–59 mo, mandatory fortification of sugar with vitamin A targeting the general population since 1998, and biofortification of maize and orange-fleshed sweet potato with provitamin A carotenoids for the general population in selected areas of the country since 2007 ( 14 , 63 ). To support these interventions, the country has laid emphasis on nutrition education programs encouraging the population to demand vitamin A–related services and adopting behavior change after public communication around diet diversification with a focus on promotion of foods rich in vitamin A ( 71 ).…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…In Zambia, VAD has been addressed as a problem of public health significance, leading to different approaches that include vitamin A capsule supplementation targeting since 1990 children aged 6–59 mo, mandatory fortification of sugar with vitamin A targeting the general population since 1998, and biofortification of maize and orange-fleshed sweet potato with provitamin A carotenoids for the general population in selected areas of the country since 2007 ( 14 , 63 ). To support these interventions, the country has laid emphasis on nutrition education programs encouraging the population to demand vitamin A–related services and adopting behavior change after public communication around diet diversification with a focus on promotion of foods rich in vitamin A ( 71 ).…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…Fortification programs are long-term interventions to prevent deficiency in areas where a major percentage of the target population consumes the selected food vehicle regularly. These interventions are costly, require oversight, infrastructure, and regulations; do not adequately target the rural poor; and overlapping interventions can cause concern for excessive intakes for some micronutrients (Tanumihardjo, Kaliwile, Boy, Dhansay, & van Stuijvenberg, 2019). Food diversification and behavior-based strategies to alleviate micronutrient deficiencies are considered ideal for long-term success in low-income countries (Nair, Augustine, & Konapur, 2016;Reinbott et al, 2016).…”
Section: Hidden Hungermentioning
confidence: 99%
“…Several recent publications have begun to assess and address the potential for excessive intake when multiple programs and interventions overlap in a community, but these are not pregnancy specific. 22,23 A study in Australia assessed the prevalence of exceeding the UL during pregnancy and found that around 20% of women exceeded the UL for iron and folate (owing to supplements). 14 However, most studies in LMIC do not report the full range of intake including the highest intake of micronutrients.…”
Section: Micronutrient Intake From Diet and Potential To Exceed The Ulmentioning
confidence: 99%